If it's not what You are looking for type in the equation solver your own equation and let us solve it.
68=3(6r-1)-7(1-3r
We move all terms to the left:
68-(3(6r-1)-7(1-3r)=0
We add all the numbers together, and all the variables
-(3(6r-1)-7(-3r+1)+68=0
| 6x12=6 | | -143=1+8(3-3b) | | 6r+4r-1=19 | | 1+y=y | | 8/180=n/6 | | y2− 1=2 | | 5/6x*2=3/8 | | 7b-5b+b-3=12 | | -3(x-9)+12=36 | | 7y-2=30 | | 20v+3v-20v=3 | | 5^2x=86 | | -22.7=x/6-3.5 | | x2=4x+10 | | 12z-11z-1=17 | | 6*x+2=4*x+20 | | 4w+4w-7w+3w-2w=6 | | 6•x+2=4•x+20 | | 6y+24(-1)=42 | | 5y+y+y-6y=9 | | 12t-9t-t+2t-t=18 | | 2.3x+1600=5.29+40x | | 8t-7t=7 | | V-v+v+2v=6 | | -2(t-4)=1-2t | | 9k-5k+5k=9 | | 6/3=8/x | | 6r+12=13 | | 9h-4h=20 | | 15q-11q=12 | | 3(3x-1)-5(2-7x)=15-(4x+4) | | 4x2+-25=0 |